Alcohol Use and Long‐Term Outcomes Among U.S. Veterans Who Received Direct‐Acting Antivirals for Hepatitis C Treatment - Kim, Nicole J. (Hepatol Commun, 2020)
Outcomes related to alcohol use after hepatitis C virus (HCV) treatment are unknown in the direct‐acting antiviral (DAA) era. We assessed levels of alcohol use before and after HCV treatment and their association with long‐term outcomes in a cohort of U.S. veterans. In this retrospective cohort analysis, 29,037 patients who initiated DAA regimens between 2013 and 2015 were followed for a mean of 3.04 years. We categorized alcohol use into three categories (nondrinking, low‐level drinking, and unhealthy drinking) using Alcohol Use Disorders Identification Test‐Consumption questionnaires administered within 1 year before (baseline) and after treatment. Multivariable Cox proportional hazards regression was used to determine the associations between alcohol use and mortality or liver‐related outcomes. Before DAA treatment, 68% of veterans reported nondrinking, 22.9% reported low‐level drinking, and 9.1% reported unhealthy drinking. Compared to patients with baseline non‐drinking, those with unhealthy drinking had a higher risk of mortality (adjusted hazard ratio [HR] 1.53, 95% confidence interval [CI]: 1.34‐1.75) and decompensated cirrhosis (adjusted HR 1.30, 95% CI: 1.06‐1.59) and lower likelihood of liver transplantation (adjusted HR 0.24, 95% CI: 0.06‐0.92). These associations were greater in patients without sustained virologic response than in those with sustained virologic response. When alcohol use before and after treatment was modeled as a time‐varying covariate, similar associations were observed. Survival analysis also found that unhealthy drinking was significantly associated with a lower probability of survival compared with nondrinking. Low‐level alcohol use was not associated with increased risk of adverse outcomes. Conclusion: In this large cohort of U.S. veterans with HCV who received DAAs, unhealthy drinking was common and associated with a higher risk of posttreatment mortality. Interventions to achieve alcohol cessation before and during antiviral treatment should be encouraged.